2002
DOI: 10.1149/1.1453410
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Nanotopography of Silicon Wafers on Post-Chemical Mechanical Polished Oxide Layers

Abstract: The impact of nanotopography of silicon wafers on the thickness homogeneity of oxide layers after deposition and chemical mechanical polishing (CMP) is investigated. Comparison of nanotopographical height with post-CMP oxide thickness for the same position on a wafer may result in inconclusive data with no obvious correlation. However, a simple relation is obtained when (i) the root-mean-square (rms) roughness of nanotopographical height false(σNHfalse), (ii) the standard deviation of post-CMP oxide thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The first mechanism is through degradation of within wafer oxide or nitride film thickness uniformity after chemical mechanical planarization (CMP), especially after the shallow trench isolation (STI) process [3]. High (low) points on the original wafer surface with spatial extent less than the planarization length of the CMP process result in locally reduced (increased) film thickness after CMP removal [4,5]. The second mechanism is the effect of nanotopography on critical dimension (CD) control.…”
Section: Site Flatness Chuck-wafer Flatness Interaction and Nanotopomentioning
confidence: 99%
“…The first mechanism is through degradation of within wafer oxide or nitride film thickness uniformity after chemical mechanical planarization (CMP), especially after the shallow trench isolation (STI) process [3]. High (low) points on the original wafer surface with spatial extent less than the planarization length of the CMP process result in locally reduced (increased) film thickness after CMP removal [4,5]. The second mechanism is the effect of nanotopography on critical dimension (CD) control.…”
Section: Site Flatness Chuck-wafer Flatness Interaction and Nanotopomentioning
confidence: 99%
“…Moreover, the authors also successfully identified prior grain boundaries on the EP surface by superimposing an AFM image of the EP surface and an AFM image of the same area after it had been treated by prior grain boundary etching. [5][6][7] In this study, new methods for observing tempered martensite microstructure are reported, including those that use EP treatment, which were reported in our previous papers, [4][5][6][7] and those that use chemical mechanical polishing (CMP), a technique used to smooth the surfaces of silicon wafers and other semiconductor materials, 8) and is a commonly used method for smoothing silicon surfaces to the atomic level without introducing the strain of polishing to the surface. This CMP technique was applied to treat the surface of the tempered martensite microstructure of medium-carbon steel covered with cementite (Fe 3 C) precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…The specimen surface must be free of any strain or unevenness [8], so in this study the authors adopted the new technique of chemical -mechanical polishing (CMP) [9], which involves the simultaneous application of chemical corrosion and mechanical polishing to prepare specimen surfaces for structural observation.…”
Section: Introductionmentioning
confidence: 99%